2021
DOI: 10.1021/acsnano.0c07242
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast, One-Step, Salt-Solution-Based Acoustic Synthesis of Ti3C2 MXene

Abstract: The current quest for two-dimensional transition metal carbides and nitrides (MXenes) has been to circumvent the slow, hazardous, and laborious multistep synthesis procedures associated with conventional chemical MAX phase exfoliation. Here, we demonstrate a one-step synthesis method with local Ti 3 AlC 2 MAX to Ti 3 C 2 T z MXene conversion on the order of milliseconds, facilitated by proton … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(79 citation statements)
references
References 31 publications
(63 reference statements)
0
76
0
Order By: Relevance
“…[ 47 ] Another novel and recent approach is a salt‐solution‐based acoustic synthesis of Ti 3 C 2 T x from Ti 3 AlC 2 , that utilized LiF in water with surface acoustic waves producing delaminated MXenes in seconds. [ 48 ]…”
Section: Mxene Synthesismentioning
confidence: 99%
“…[ 47 ] Another novel and recent approach is a salt‐solution‐based acoustic synthesis of Ti 3 C 2 T x from Ti 3 AlC 2 , that utilized LiF in water with surface acoustic waves producing delaminated MXenes in seconds. [ 48 ]…”
Section: Mxene Synthesismentioning
confidence: 99%
“…Recently, it has been shown that the selective etching of Al layers from the Ti 3 AlC 2 MAX phase for the synthesis of Ti 3 C 2 T x MXene using a salt-based method has been improved with the help of surface acoustic waves (SAWs), which produce protons. Then, the combination of these protons with fluorine ions from LiF helps to selectively etch the MAX phase into MXene [140].…”
Section: Top-down Synthesis Approachesmentioning
confidence: 99%
“…This method was first introduced in paper I; it merges light "localized HF" etching and surface acoustics through localized mechanical vibrations, i.e., SAW (34) . The physics behind the SAW will be discussed in detail in chapter Chapter 4 Surface Acoustic Waves (SAW)…”
Section: Salt-solution-based Acoustic Synthesis Of Mxenementioning
confidence: 99%